The influence of variety seeking, alternative attractiveness, subjective norm, and satisfaction on switching intention - Qurrati A'yun; Firman (Universitas Negeri Padang, 2023)
Competition in the smartphone industry is very tight, marked by the emergence of more and more new products with various brands. The development of the times and science have had an impact on the tendency of consumer behavior to change, especially in terms of consumption. So that a phenomenon appears in society in the form of consumer behavior that is easy to move around in consuming a product or service. This study aims to analyze the effect of variety seeking, alternative attractiveness, subjective norms, and satisfaction to switching intention on smartphones Iphone in Padang City. The sample used in this study was 170 respondents with the criteria of people who live in the city of Padang and are currently using an Iphone. Research data was collected using a questionnaire through the Google form. This study was analyzed using IBM SPSS Statistics 26. The results of this study indicate that variety seeking, alternative attractiveness, and subjective norms have a positive and significant effect on switching intention, satisfaction has a negative and significant effect on switching intention.